LAPS-HEURISTIC Learning Model Improves Mathematical Problem-Solving Ability - Ni Made Wiyasmei Gyanthi; I Gusti Ayu Tri Agustiana; Dewe Gede Firstia (International Journal of Elementary Education, 2023)
Mathematics learning still needs to show more optimal results. The results of the data analysis found that around 10% of the total students were below the KKM. This research aims to analyze the application of the LAPS learning model to the problem-solving abilities of fifth-grade elementary school students. This type of research is quantitative research. The design used is a quasi-experiment. The experimental design used is the Nonequivalent Control Group Design. The population in this study is class V in elementary school, with as many as 126 students. The sampling technique uses simple random sampling. The number of samples is 28 students. The method of collecting data is a test. The data collection instrument was a test in the form of an essay. The data analysis technique used is descriptive analysis and inferential statistics. The research results are that the LAPS-Heuristic learning model significantly affects the math problem-solving abilities of fifth-grade elementary school students. It was concluded that the LAPS-Heuristic learning model could improve the math problem-solving abilities of fifth-grade elementary school students. This research implies that using the LAPS-Heuristic learning model makes students feel happy in learning mathematics, so it has an impact on students' understanding and problem-solving abilities to increase.